Condição corporal e jejum sobre o metabolismo energético e crescimento de juvenis de pacu - Favero, Gisele Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The objective of this study was to evaluate the metabolic strategies of pacu (Piaractus mesopotamicus) using fasting and refeeding as a tool. In the first experiment, 450 pacu were divided into 18 tanks of 250 L, at the following treatments: fed for 60 days (control) with formulated diet, and subjected to short alternating cycles of six days of fasting and six of refeeding (6/6); and subjected a long period of 30 days of fasting and refeeding for 30 days (30/30) during 60 days. Each six days 12 fish, per treatment, were sampled to determine the blood variables (glucose and serum triglyceride, cholesterol, fatty acids, and total serum protein) and tissue (glycogen and hepatic lipid, hepatosomatic index (HSI), muscle protein and lipid and mesenteric fat index (MFI)). At the beginning and end of the experiment were determined growth parameters (weight gain (WG), specific growth rate (SGR), food intake, protein efficiency ratio (PER), feed conversion ratio (FCR) and condition factor (K)). Fasting for treatments 6/6 and 30/30 was marked by the use of glucose and plasma triglycerides and increased serum cholesterol and fatty acids. In addition, there was a decrease of glycogen and liver lipid and muscle lipid. On refeeding, both treatments showed rapid recovery of energy reserves. However, the refeeding periods were not sufficient for fish growth recovery. In a second study, 204 fish were kept in 12 tanks of 430 L and separated into two pre trial groups, fed with different diets for 15 days, to obtain different body conditions (lean and fat fish), in terms of mesenteric fat content. After reaching different body conditions, both groups were submitted to treatments: continuously fed for 20 days with formulated diet (control) and subjected to 15 days of fasting and re-fed for five days with formulated diet. At the beggining, on the 15th and 20th (final) days of the experimental period, nine fish per treatment were sampled to determine the ...

O objetivo desse estudo foi avaliar as estratégias metabólicas do pacu (Piaractus mesopotamicus) utilizando jejum e realimentação como ferramenta. No primeiro experimento, 450 juvenis de pacu foram alocados em 18 tanques de 250 L, nos seguintes tratamentos: alimentados durante 60 dias (controle) com dieta formulada, submetidos a ciclos curtos e alternados de seis dias de jejum e seis de realimentação (6/6) e submetidos a um ciclo longo de 30 dias de jejum e 30 de realimentação (30/30), durante 60 dias. A cada seis dias, 12 peixes de cada tratamento eram amostrados para determinação das variáveis sanguíneas (glicose e triglicerídeo plasmáticos, colesterol, ácidos graxos e proteína total séricas) e teciduais (glicogênio, lipídeo hepático e índice hepatossomático (IHS), lipídeo e proteína muscular e índice de gordura víscero-somática (IGVS)). Ao início e final do período experimental foram determinadas as variáveis de crescimento (ganho em peso (GP), taxa de crescimento específico (TCE), consumo, taxa de eficiência protéica (TEP), conversão alimentar (CA) e fator de condição (K)). O jejum para os tratamentos 6/6 e 30/30 foi marcado pela utilização de glicose e triglicerídeos plasmáticos e aumento do colesterol e ácidos graxos séricos. Também ocorreu diminuição do glicogênio e lipídeo hepático e do lipídeo muscular. Com a realimentação, ambos os tratamentos apresentaram rápida recuperação das reservas energéticas. Porém, os tempos de realimentação estabelecidos não foram suficientes para a recuperação do crescimento dos peixes. Em um segundo estudo, 204 peixes foram alocados em 12 tanques de 430 L e divididos em dois grupos pré-experimentais, sendo alimentados com diferentes dietas durante 15 dias para a obtenção de grupos com duas condições corporais (peixes magros e gordos), definidos pela concentração de tecido adiposo mesentérico. Após alcançarem condições corporais ...
Keywords: Peixe; Pacu (Peixe); Restrição calórica; Desempenho; Metabolismo energetico; Fishes